Missed Diagnosis of Perforation and Intraperitoneal Migration of an Intrauterine Device and Its Management in a Resource-Limited Setting: A Case Report - Gebremichael A; Teka H; Abadi KK; Siferih M; Moges M; Arusi M; Shiferaw A (International Medical Case Reports Journal, 2024)
Akebom Gebremichael,1 Hale Teka,2 Kidus Kebede Abadi,3 Melkamu Siferih,4 Menberu Moges,5 Muhudin Arusi,1 Abel Shiferaw6 1Department of Obstetrics and Gynecology, St. Peter’s Specialized Hospital, Addis Ababa, Ethiopia; 2Department of Obstetrics and Gynecology, College of Health Science, Mekelle University, Mekelle, Tigray, Ethiopia; 3Department of Obstetrics and Gynecology, Riwyet Maternal and Child Health Center, Tigray, Ethiopia; 4Department of Obstetrics and Gynecology, Debre Markos University, Debre Markos, Ethiopia; 5Department of Obstetrics and Gynecology, Tayo Hospital, Baidoa, Somalia; 6Department of Obstetrics and Gynecology, Dessie Comprehensive Specialized Hospital, Dessie, EthiopiaCorrespondence: Akebom Gebremichael, Email kidanemariamakebom@gmail.comBackground: The intrauterine device is a popular and highly effective form of long-acting reversible contraception. Although generally safe, complications could happen. One of the most serious complications of intrauterine device use is uterine perforation. Risk factors for perforation include, but are not limited to, postpartum period, breastfeeding, levels of experience, and excessive force exerted during insertion. This case is significant because it demonstrates risk factors for uterine perforation, how to handle missing strings, and care in places with little resources.Case Presentation: We discuss the case of a 27-year-old black Ethiopian woman who presented with chronic pelvic pain and had a perforated intrauterine device discovered in the cul-de-sac. The device had been inserted at six weeks postpartum. The client was unable to feel the strings three months after insertion, and a wrong diagnosis of expulsion was made. After one year of insertion, the intrauterine device was located on a plain abdominal radiograph and removed via laparotomy without complications.Conclusion: Although uterine perforation is a rare complication of intrauterine device insertion, special attention should be paid to women with risk factors. In the absence of a witnessed expulsion, assessments and investigations should be carried out before declaring a device expelled. In patients with chronic pelvic pain complaints in the presence of an intrauterine device, perforation and migration outside the uterine cavity should be considered. Abdominal X-rays and laparotomies can be used to find and manage extrauterine migrating devices in environments with limited resources.Keywords: intrauterine device, missed uterine perforation, intraperitoneal migration